Analysis Of Musculoskeletal Drivers Literature: A Comprehensive Review Of Scientific Publications - Setyo Nugroho, Bayu Yoni; Pramitasari, Ratih; Treesak, Chalobon; Ximenes, Adriano (Universitas Ahmad Dahlan, 2025)
Background:Musculoskeletal disorders among professional drivers represent a significant occupational health challenge, with prevalence rates of 78.6% globally, causing physical discomfort, reduced performance, and increased workplace injury risks. The objective of this study is to provide a comprehensive overview of MSD research development and guide future research directions based on quantitative analysis of scientific publications. Method: A comprehensive bibliometric analysis was conducted using Web of Science database data from August 10, 2025. The search included open access English articles on